CISTO PERIAPICAL: REVISÃO - Martins, Anna Karina; Camargo, Ana Júlia; Girelli, Raíssa Alba; Slaviero, Renata; Senger, Franciane Rios; Tomazeli, Karin Berria (Anais de Odontologia / ISSN 2526-9437; v. 3 n. 1 (2018): 2018/1, 2018)
.